Análise da interface adesiva entre pinos de fibra de vidro e dentina intrarradicular submetida à irrigação com diferentes agentes condicionantes - Suzuki, Thaís Yumi Umeda [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The purpose of this study was to evaluate the interaction of conditioning agents and resin cements in the luting procedure of glass fiber posts in different thirds of intra-root dentin, through the bond strength test, mechanical properties and sealing ability of the adhesive interface. Ninety single-rooted premolares human teeth were used in this study. After endodontic filling and mechanical preparation of root canal, teeth were divided into five groups according to the conditioning agents (distilled water, 5.25% sodium hypochlorite, 25% polyacrylic acid, 2% chlorhexidine and 23 ppm silver nanoparticles dispersion). Three adhesive cementation technique were adopted: Group 1: ScotchbondTM Universal self-etching adhesive + RelyX ARC resin cement, Group 2: RelyX U200 self-adhesive resin cement, Group 3: Maxcem Elite self-adhesive resin cement. The mechanical properties (Martens hardness and elastic modulus) of the adhesive interface structures (resin cement and underlying dentin) were measured in a DUH-211 digital ultra-microhardness tester (Shimadzu), under load of 5mN in different areas of intra-root dentin (cervical, middle and apical). Push-out bond strength was measured in a universal testing machine (Emic DL 3000). Sealing ability was quantified with a fluid-filtration system (Flodec) during 5 min was immediately measured. The data of bond strength and mechanical properties were subjected to statistical tests of normality and analyzed by ANOVA for repeated measures and Fisher's test (α=0.05). The results showed that the mechanical properties of Martens hardness and elastic modulus of resin cements and the underlying dentine can be influenced by conditioning agents, as well as the depth of intraradicular dentin. The same phenomenon was observed in the push-out bond strength test. The 23ppm silver nanoparticle dispersion...

O propósito deste estudo foi avaliar a interação das soluções irrigantes e tipos de cimentos resinosos na cimentação de pinos de fibra de vidro nos diferentes terços da dentina intrarradicular, através do teste de resistência de união, avaliação das propriedades mecânicas e capacidade de selamento da interface adesiva. Noventa dentes pré-molares humanos unirradiculares foram utilizados neste estudo. Após obturação endodôntica e preparo mecânico dos condutos radiculares, os dentes foram divididos em 5 grupos de acordo com os agentes condicionantes (água destilada, hipoclorito de sódio 5,25%, ácido poliacrílico 25%, clorexidina 2%, dispersão de nanopartículas de prata à 23 ppm) e subdivididos em 3 grupos experimentais (n=6), de acordo com a técnica adesiva adotada para cimentação de pinos de fibra de vidro: Grupo SBU: adesivo autocondicionante ScotchbondTM Universal + cimento resinoso convencional RelyX ARC; Grupo U200: cimento resinoso autoadesivo RelyX U200; Grupo MCE: cimento resinoso autoadesivo Maxcem Elite. As propriedades mecânicas de dureza e módulo de elasticidade das estruturas da interface adesiva (cimento resinoso e dentina subjacente) foram mensuradas em ultramicrodurômetro digital DUH-211 (Shimadzu), sob carga de 5mN nos diferentes terços da dentina intrarradicular (cervical, médio e apical). A resistência de união foi mensurada pelo teste de push-out em máquina de ensaio universal (Emic DL 3000). A capacidade de selamento foi quantificada através de um sistema de infiltração de fluido (Flodec) durante 5 minutos. Os dados de resistência de união, propriedades mecânicas e capacidade de selamento foram submetidos a testes estatísticos de normalidade e analisados pela ANOVA para medidas repetidas e teste de Fisher (α = 0,05). Os resultados mostraram que as propriedades mecânicas de dureza...
Keywords: Cimentos de resina; Técnica para retentor intrarradicular; Dentina; Adesivos dentinários; Nanopartículas; Prata